1993
DOI: 10.1002/gps.930080505
|View full text |Cite
|
Sign up to set email alerts
|

Supporting everyday activities in dementia: An intervention study

Abstract: SUMMARYThe efficacy of an intervention programme designed to support performance in activities of daily living was investigated in four patients with dementia at different levels of severity of impairment. Important features ofthe programme included that (a) task conditions should be highly supportive, (b) the importance of episodic and semantic memory skills for successful performance should be minimized, (c) an acceptable performance level should be possible to achieve using skills that are relatively well p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…Several studies have focussed on the ef®cacy of such procedural memory stimulation programmes. Josephsson et al (1993) demonstrated that performance of three out of four patients with moderate to severe dementia can be signi®cantly improved from baseline when environmental support is provided. These performance gains can be maintained even when support is no longer present, at least in the moderate stage of the disease (case OB).…”
Section: Sensorimotor Skill Stimulationmentioning
confidence: 98%
“…Several studies have focussed on the ef®cacy of such procedural memory stimulation programmes. Josephsson et al (1993) demonstrated that performance of three out of four patients with moderate to severe dementia can be signi®cantly improved from baseline when environmental support is provided. These performance gains can be maintained even when support is no longer present, at least in the moderate stage of the disease (case OB).…”
Section: Sensorimotor Skill Stimulationmentioning
confidence: 98%
“…RCTs of intervention for people with dementia were hard to identify, with just one study of cognitive stimulation noted in France (Breuil et al, 1994). However, controlled investigations of reality orientation in Italy (Zanetti et al, 1995) and memory clinicbased multi-component intervention in the UK (Moniz-Cook, Agar, Gibson, Win, & Wang, 1998) as well as single case studies of cognitive rehabilitation in Italy and Sweden (Josephsson et al, 1993;Zanetti et al, 1997) demonstrated that promising interventions were emerging.…”
Section: Psychosocial Intervention Research: a Historical Perspectivementioning
confidence: 99%
“…Cognitive rehabilitation has been found successful in teaching individuals with dementia [22]- [24] and MCI [25] to learn or re-learn information, maintain information over time, apply information to everyday contexts, develop strategies to compensate for memory impairment, and adjust the environment to reduce memory demands [26]- [28]. Cognitive rehabilitation theory (CRT) is multi-dimensional and emphasizes the importance of an individual's personal context, environmental context, and social system [29].…”
Section: Cognitive Rehabilitation Overviewmentioning
confidence: 99%